Porous high-Tc superconducting cuprates: Advantages and applications. (September 2019) - Koblischka, M. R.; Koblischka-Veneva, A.; Pavan Kumar Naik, S.; Gokhfeld, D.; Murakami, M.
Abstract: Porous high- T c superconducting cuprates are promising materials representing an alternative preparation route to enable the fabrication of large-scale, light-weight superconducting samples. There are several advantages of such samples including the much easier (and faster) oxygenation process, a simpler scalability to produce large samples, and of course, the reduced weight. Two different types of such samples were prepared in the literature: (i) Superconducting foams, prepared using polyurethane foams converted to green phase foams followed by an infiltration growth (IG) process. (ii) Superconducting nanowire networks prepared by spinning from sol-gel precursors. Such fabric-like nanowire networks are extremely light-weight, but show very interesting properties. We discuss the properties of such samples concerning both the physical parameters and the respective microstructures and give an overview about possible applications.